At-Tashbīh fī Khuṭub Khulafā’ ar-Rāshidīn (Dirāsah Balāghiyyah Bayāniyyah) - Muhammad Zaki; Fitri Setyo Rini; Arsyad Muhammad Ali Ridho; Muhammad Wahyudi (An-Nahdah Al-'Arabiyah)
This article presents a rhetorical and illustrative study of similes in the speeches of the Rashidun Caliphs, highlighting the use of similes as a prominent rhetorical tool employed by the caliphs to enhance meanings and clarify ideas. The article reviews various types of similes and their usage in different contexts to effectively convey messages. The research aims to explore the aesthetic and communicative effectiveness of these rhetorical devices in conveying profound meanings and engaging the audience. Utilizing a library research method, the study meticulously examines historical texts, analyzing the frequency, context, and stylistic nuances of similes used by the Caliphs. The findings reveal a rich tapestry of similes that not only enhance the eloquence of the speeches but also serve to clarify complex ideas, reinforce moral teachings, and evoke emotional responses from listeners. This research highlights the enduring impact of these rhetorical strategies on Islamic oratory and their contribution to the persuasive power of the Caliphs' speeches. In conclusion, the study underscores the significance of similes in Islamic rhetorical tradition, demonstrating their role in shaping the legacy of the Rightly Guided Caliphs' discourse.